A systematic review of Aspilia africana (Pers.) C.D. adams traditional medicinal uses, phytoconstituents, bioactivities, and toxicities - Roggers Gang; Denis Okello; Yeongjun Ban; Youngmin Kang (Pharmacological Research)
Aspilia africana (Pers.) C. D. Adams, popularly referred to as wild sunflower, has been used for generations across several African communities to treat various diseases, including malaria, wounds, osteoporosis, diabetes mellitus, gastric ulcers, measles, tuberculosis, stomach ache, rheumatic pains, and gonorrhea. This study aimed to systematically and critically compile data on the traditional medicinal uses, phytochemistry, bioactivities, botanical descriptions, and toxicities of A. africana. Relevant research findings were retrieved and organized from various databases, including PubMed and ScienceDirect, in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. To date, 149 phytochemicals have been identified from various A. africana parts and they primarily belong to the classes of terpenoids, lipids, hydrocarbons, phenolics, and esters. The extracts and bioactive phytochemicals of A. africana have revealed several pharmacological properties, including antimalarial, anticancer, wound healing, anti-inflammatory, antidiabetic, and antimicrobial activities. However, the major components responsible for these bioactivities and their mechanisms of action in some diseases have not yet been clearly identified. Additionally, toxicity and clinical trial data for A. africana are limited with most toxicological assessments being acute in nature. Therefore, further research on the mechanisms of action of the pure bioactive phytochemicals and toxicity of A. africana are necessary to better understand its efficacy and safety. Taken together, this study provides comprehensive information on the traditional medicinal uses, phytochemistry, bioactivities, and toxicity of A. africana, and a reference for future studies, relevant to the development of therapeutic products.